Corporate environmental performance: Revisiting the role of organizational slack - Symeou, Pavlos C.; Zyglidopoulos, Stelios C.; Gardberg, Naomi A. (My University, 2019)
To date, there has been little agreement on the role of organizational slack in firms' Environmental Performance (EP). Drawing on the Behavioral Theory of the Firm (BTOF), we advance this line of inquiry by conceptualizing the distinct effects that absorbed slack and unabsorbed slack have on EP as well as how industry discretion, firm-specific regulatory pressures, and EP-aspiration levels moderate these effects. We test our hypotheses with a unique panel of 753 US public firms for the period 1991–2008. As hypothesized, our findings indicate that unabsorbed slack has a positive effect on EP, while absorbed slack has a negative one. Industry discretion, firm-specific regulatory pressures, and EP aspiration levels moderate these relationships in distinct ways. We discuss the implications of our research on managerial and policy decision-making.
Keywords: Absorbed slack; Environmental performance; Organizational slack; Unabsorbed slack